Visual Block-based Programming for ICT Training of Prospective Teachers in Morocco - Ouahbi, Ibrahim; Darhmaoui, Hassane; Kaddari, Fatiha (International journal of modern education and computer science, 2022)
We conducted a training experimentation on computer coding whose aim is to probe ICT skills enhancement of pre-service teachers in Morocco. For that, we have developed and implemented training sessions using a visual programming tool (Scratch) targeting 63 prospective teachers at the Faculty of Educational Sciences (FSE) and the Regional Center for Education and Training Professions (CRMEF) in Nador, Morocco. During these sessions, trainees were introduced to algorithmic thinking where they implemented teaching sequences in their specialty subjects using Scratch. Pre and post surveys were conducted to measure the evolution of the trainees’ perceptions towards the integration of computer coding in the teaching and learning of their specialties. The analysis of the surveys showed the potential of integrating computer coding in the development of learners’ transversal skills. The training revealed different possibilities of exploiting visual block-based programming environments in the teaching and learning process.